Evaluation of Glucose-Infused Ceramic Separators in Microbial Fuel Cells - Hodaka Shimohata; Trang Nakamoto; Taguchi Kozo (Environmental Science and Sustainable Development, 2025)
Recently, global energy demand has been increasing. Most of the energy is produced from fossil fuels. Since fossil fuels are finite and produce greenhouse gases during energy creation, alternatives are needed. Microbial fuel cells (MFCs) are a promising source of renewable energy. These cells utilize ceramic separators, and enhancing the performance of these separators is crucial for increasing the power output of MFCs. In this experiment, ceramic separators were fabricated with varying volumes of glucose. During the firing process, the glucose dissolves, resulting in separators with porous properties. The performance of MFCs with these glucose-infused separators was evaluated. The results showed that ceramic separators mixed with glucose had significantly more small holes in their surface compared to those without glucose. This increased porosity enhances proton transport, thereby improving the performance of the separator. Consequently, MFCs using these separators demonstrated higher power output, with the cathode performing better as the glucose content in the separator increased. This indicates that glucose-infused ceramic separators are effective in improving MFC performance.